Lejeunea apiahyna, a new synonym of Lejeunea cristuliflora (Lejeuneaceae, Marchantiophyta) - Bastos, Cid José Passos (Phytotaxa, 2018)
Lejeuneaceae is the largest liverwort family with more than 1800 species in about 70 genera (Zhu et al. 2017). Lejeunea Libert (1820: 373) is the second largest genus of Lejeuneaceae with many taxa poorly known (He et al. 2012). Lejeunea apiahyna (Stephani 1914: 514) Singh (2013: 63) is one of those poorly known species and is known only from Brazil. It was described by Stephani (1914) as Otigoniolejeunea apiahyna Stephani (1914: 514) based on J. Puiggari’s collection from the State of São Paulo, Brazil, and transferred to the genus Lejeunea by Singh (2013). According to Wei et al. (2014), Otigoniolejeunea Spruce (1884: 77) is represented by only two ocellus containing species: Otigoniolejeunea huctumalcensis (Lindenberg & Gottsche in Gottsche et al. 1847: 762) Wei et al. (2014: 237), and Otigoniolejeunea portoricensis (Hampe & Gottsche 1853: 352) Wei et al. (2014: 237).